Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

Express the given function:

[tex]\[ y = 3x^4 - 2x^2 + 8 \][/tex]


Sagot :

Let's solve the function \( y = 3x^4 - 2x^2 + 8 \) step by step for a specific value of \( x \).

### Step-by-Step Solution:

1. Identify the function:
\( y = 3x^4 - 2x^2 + 8 \)

2. Choose a value for \( x \):
Let's take \( x = 2 \) as our example value.

3. Substitute \( x = 2 \) into the function:
[tex]\[ y = 3(2)^4 - 2(2)^2 + 8 \][/tex]

4. Compute \( 2^4 \):
[tex]\[ 2^4 = 16 \][/tex]

5. Plug this back into the equation:
[tex]\[ y = 3 \cdot 16 - 2(2^2) + 8 \][/tex]

6. Compute \( 3 \cdot 16 \):
[tex]\[ 3 \cdot 16 = 48 \][/tex]

7. Compute \( 2^2 \):
[tex]\[ 2^2 = 4 \][/tex]

8. Compute \( 2 \cdot 4 \):
[tex]\[ 2 \cdot 4 = 8 \][/tex]

9. Substitute these values back into the function:
[tex]\[ y = 48 - 8 + 8 \][/tex]

10. Simplify the expression:
[tex]\[ y = 48 - 8 + 8 = 48 \][/tex]

So, for \( x = 2 \), the value of the function \( y = 3x^4 - 2x^2 + 8 \) is \( y = 48 \).

Therefore, the result is
[tex]\[ y = 48 \][/tex]